Positive Feedback Loop of OCT4 and c-JUN Expedites Cancer Stemness in Liver Cancer. (11th July 2016) - Kuo, Kung-Kai; Lee, King-Teh; Chen, Ker-Kong; Yang, Ya-Han; Lin, Ying-Chu; Tsai, Ming-Ho; Wuputra, Kenly; Lee, Yen-Liang; Ku, Chia-Chen; Miyoshi, Hiroyuki; Nakamura, Yukio; Saito, Shigeo; et al.
Abstract: The network of stemness genes and oncogenes in human patient-specific reprogrammed cancer stem cells (CSCs) remains elusive, especially in liver cancer. HepG2-derived induced pluripotent stem cell-like cells (HepG2-iPS-like cells) were generated by introducing Yamanaka factors and the knockdown vector shTP53. They exhibited features of stemness and a higher tumorigenesis after xenograft transplantation compared with HepG2 cells. The cancerous mass of severe combined immunodeficiency (SCID) mice derived from one colony was dissected and cultured to establish reprogrammed HepG2-derived CSC-like cells (designated rG2-DC-1C). A single colony exhibited 42% occurrence of tumors with higher proliferation capacities. rG2-DC-1C showed continuous expression of the OCT4 stemness gene and of representative tumor markers, potentiated chemoresistance characteristics, and invasion activities. The sphere-colony formation ability and the invasion activity of rG2-DC-1C were also higher than those of HepG2 cells. Moreover, the expression of the OCT4 gene and the c-JUN oncogene, but not of c-MYC, was significantly elevated in rG2-DC-1C, whereas no c-JUN expression was observed in HepG2 cells. The positive-feedback regulation via OCT4-mediated transactivation of the c-JUN promoter and the c-JUN-mediated transactivation of the OCT4 promoter were crucial for promoting cancer development and maintaining cancer stemness in rG2-DC-1C. Increased expression of OCT4 and c-JUN was detected in the early stage of human liver cancer. Therefore, the positive feedback regulation of OCT4 and c-JUN, resulting in the continuous expression of oncogenes such as c-JUN, seems to play a critical role in the determination of the cell fate decision from iPS cells to CSCs in liver cancer. Abstract : The OCT4/c-JUN positive feedback loop found in reprogrammed HepG2-derived cancer stem cell-like cells (rG2-DC-1C) sheds light on the tumorigenesis of liver cancer. 4F, Yamanaka 4 factors; iPS-like cells, induced pluripotent stem-like cells.